Applicability of creatinine-based glomerular filtration rate assessment equations to patients with neurogenic bladder - He, Panqi; Liao, Limin (Frontiers in Physiology, 2024)
PurposeGlomerular filtration rate (GFR) measured by dynamic renal scintigraphy (Gates method) is used in this study as the standard to investigate the applicability of two creatinine (Cr)-based GFR estimation equations in Chinese patients of different genders, age groups, and GFR stages diagnosed with neurogenic bladder (NB).MethodsGFR values were measured using 99mTc-DTPA renal dynamic imaging, the new serum creatinine (Cr)-based chronic kidney disease epidemiology collaborative group (CKD-EPI) equation, and the equation for the estimated GFR of CKD patients in China, which were designated as sGFR, EPI-GFR, and cGFR, respectively. Pearson’s correlation and linear regression were used to compare the differences, absolute differences, precision, and accuracies of the results of the two equations with sGFR to determine the formula offering better performance for the assessment of patients with NB.ResultsMeasurements from a total of 99 patients with NB were used in the final analysis. Both cGFR and EPI-GFR were moderately correlated with sGFR in both men and women. The overall staging accuracies of EPI-GFR and sGFR were significantly higher than that of cGFR. Among the patients staged, only those with GFRs in the range of 60–89 mL/min/1.73 m2 had moderate correlations between cGFR, EPI-GFR, and sGFR, while the remaining patients had low correlations.ConclusionResearchers found that the equation developed for Chinese CKD patients performed well for patients with NB aged 20–25 years, while the race-neutral CKD-EPI equation performed better in NB patients aged 26–35 years.